2004
DOI: 10.1016/s0002-9440(10)63256-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Scrapie-Induced Pathology of the Retina and Brain in Transgenic Mice that Express Hamster Prion Protein in Neurons, Astrocytes, or Multiple Cell Types

Abstract: Prion protein (PrP) is expressed in many tissues and is required for susceptibility to scrapie and other prion diseases. To investigate the role of PrP expression in different cell types on pathology in retina and brain after scrapie infection, we examined transgenic mice expressing hamster PrP from the PrP promoter (tg7), the neuron-specific enolase promoter (tgNSE), or the astrocyte-specific glial fibrillary acidic protein promoter (tgGFAP). After intraocular inoculation with hamster scrapie, clinical diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…Therefore, we established a PMCA reaction using as substrate brain homogenates from tg7 hamster PrP transgenic mice, which express 4-to 5-fold more PrP than hamsters (31). 263K scrapie brain from a terminal stage tg7 mouse containing PrPres was used at a 1:100 dilution to seed the PMCA reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we established a PMCA reaction using as substrate brain homogenates from tg7 hamster PrP transgenic mice, which express 4-to 5-fold more PrP than hamsters (31). 263K scrapie brain from a terminal stage tg7 mouse containing PrPres was used at a 1:100 dilution to seed the PMCA reaction.…”
Section: Resultsmentioning
confidence: 99%
“…scrapie infection gave 90 to 100% incidence of neuroinvasion and clinical scrapie with incubation periods somewhat longer than the i.c. (35). Therefore, lack of PrP anchoring, rather than low PrPsen levels, appears to account for the low incidence of neuroinvasion seen after i.p.…”
Section: Discussionmentioning
confidence: 98%
“…4), which may be directly linked to the more pronounced prion accumulation in these animals. Numerous studies have demonstrated that astrocytes are host cells for prion replication in vitro and in vivo (14,16,32,34,48,53,74). Moreover, in vitro astrocyte activation and proliferation were previously shown to result directly from exposure to PrP Sc (21,23,25).…”
Section: Discussionmentioning
confidence: 99%